Sweetpotato (SP-30) Flakes: Process Optimization and Moisture Adsorption Isotherm Studies - Tan, Julie D.; Tan, Daniel Leslie S.; Alumbro, Adrian C. (Annals of Tropical Research, 2014)
Sweetpotato is one of the predominant crops grown by local farmers in the marginal uplands of Brgy. Linao, Sitio Batuan, Inopacan, Leyte. The need to produce quality food products from sweetpotato is a continuing challenge to open new opportunities for farmers and entrepreneurs alike. This study aimed to determine the potential of sweetpotato var. SP30 for flake production and conduct moisture adsorption isotherm studies. Two screening processes were made using the 7-variable 8-run Plackett-Burman design while a face centered Central Composite Design (CCD) was employed during optimization. Sensory evaluation results were subjected to response surface regression (RSREG) analyses to generate optimum processing condition(s). Moisture adsorption studies were carried out to determine the nature of the product isotherm based on Brunauer-Deming-Deming-Teller (BDDT) classifications. Fitting of data was done using the Bruanauer-Emmett and Teller (BET) and Guggenheim-Anderson de Boer (GAB) models to determine the amount of adsorbed moisture in the product during storage at different temperature levels. Screening results identified Drying time (Dt), Drying Temperature (DT) and Oven Toasting time (OTt) as the critical processing variables. A set of combinations of Dt (min.), DT (⁰C), and OTt (min.) were generated as a result of the optimization. These combinations were 75-50-20, 80-50-20, 80-50-18, 85-50-20 and 90-50-20. Calculated values for the mass fraction of adsorbed water in the monolayer (WmB and WmG ) at 30 ⁰C, 40 ⁰C and 50 ⁰C are 0.0971, 0.1311, 0.0591 and 0.1046, 0.2447 and 0.2224 respectively (expressed in g/100gH2O). Sweetpotato (var. SP30) was found suitable for flake production. Moisture adsorption isotherm of sweetpotato flakes was sigmoid in shape and classified as type II in the BDDT classification. Wm values for both BET and GAB were found to follow the relationship WmB and WmG (Timmerman, 2003).